THE IMPACT OF THE EXTREME IDEAS REFLECTIONS ON THE PSYCHOLOGICAL STABILITY OF THE SOCIETY - IBRAHIM , MUHAMMAD (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the worlds, and prayers and peace be upon the best of his creation and the seal of prophets and his messengers, our Prophet Muhammad, peace and blessings be upon him and his family This is the abstract of my research, which is under the title (The impact of intellectual extreme repercussions on the psychological stability of society) because the society is considered as the base that nations built on. In fact, our Islamic society now a day suffers from great challenges and dangerous phenomena led sometimes to lose its internal security, coherence and the dispersion of its people into different levels such as the believing level, ethical level and the psychological level. The world witnesses many sequenced changes that carry thoughts with different directions. The owners of the mentioned thoughts try to spread them by using modern media, which have great and fast impacts on the psychological stability of the society members. The importance of this research shows the fact that after the appearance of ISIS daish, the Iraqi community suffers from various problems such as the instability and unbalance that lead to social, psychological, healthy problems. The main reason behind choosing this subject is to keep the society stable and balance is regarded as a doctrinal origin founded in lots Qur'anic texts and for it, many rules were constructed. Religious men must clarify the idea that all what happened to us had happened before to our prophet Muhammad peace and blessings of Allah be upon him and to his fellows. We must know the fact that the believer is afflicted in his all affairs. Even we should get rid of the negative thoughts. The research includes preface, an introduction carries the title definitions and three sections. The first section tackles the intellectual extreme reasons. The second one shows the impact of intellectual extreme repercussions on the psychological stability of society. The third section mentions the answers and solutions for the intellectual extreme repercussions. Followed by an end and a bibliography. Praise be to Allah, Lord of the worlds, and prayers and peace be upon his honest messenger, our Prophet Muhammad, peace and blessings be upon him and his family and companions.